Fully moral artificial agents: future or fiction - Moore, Jaimee (Department of Philosophy, 2025)
The rapid technological progress has resulted advancements in technology that includes the development of Artificially Intelligent agents (AI) for various purposes. The extensive progress in AI has reached a point where the introduction of AI agents as android robots or humanoids into society is plausible. This highlights the evolving relationship between humans and technology. This thesis explores the multidimensional aspects of artificial intelligence (AI) by examining the intersection of machine ethics, ethical theories, and deep learning. The central focus is on assessing the compatibility of ethical theories with the rapid advancements in technology, particularly the potential development of fully moral artificial agents. The aim of this thesis is to address the ethical concerns associated with the evolution of AI, particularly the introduction of artificially intelligent agents into various societal roles, such as care robots in healthcare. The need for an impartial approach to address these concerns is identified, leading to the proposal of machine ethics as a framework. Machine ethics, defined as ensuring moral behaviours in AI, provides a basis for evaluating the ethical capabilities of artificially intelligent agents. As technology continues to progress, the demand for a comprehensive ethical framework for AI decision-making becomes increasingly apparent. Machine ethics offers insights into the ethical processes involved in AI decision-making, allowing a closer examination of computational abilities and ethical capacities. The primary inquiry revolves around whether AI agents can achieve full morality and if existing ethical theories can govern their behaviour effectively. To explore these questions, the thesis draws upon three ethical theories—Utilitarianism, Deontology, and African Ubuntu Ethics—and their applicability to the development of fully moral artificial agents. It employs deep learning as a critical component in understanding moral agency within the context of AI. The analysis unfolds in four parts: first, providing a background on AI concepts; second, examining recent AI progress and the potential for ethical AI agents; third, exploring the future of AI in relation to morality through ethical theories; and fourth, establishing criteria for considering AI agents as moral agents. In conclusion, the thesis argues that, with the advancements in technology and the insights provided by machine ethics and ethical theories, the development of fully moral artificial intelligent agents is possible.